Sistem Pakar Berbasis Android Untuk Diagnosa Penyakit Mata Pada Manusia - Sikumbang, Erma Delima; Illahiya, Elfa; Mustika, Wida Prima (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The eye is one of the most valuable gifts of the creator. Besides being used for looking, senses of vision are also very influential in various human activities. It takes a healthy eye to avoid being disturb. One of them is an eye disease, and we often forget to treat it well because of less public knowledge to prevent eye diseases. That's why it’s needed an expert system for diagnosing and classify diseases eye of humans, which play a role in replacing and imitate the reasoning process of an expert in solving a problem. And can give the right and fast solution to be able to help an expert to diagnosing diseases stored in the database system. In this research, an expert system was built based on Android Mobile with the use of programming language Android Studio. This application exerts system uses the forward chaining method, aims to trace the symptoms that appear in the form of questions to diagnose the type of disease that can recognize the type of disease after consulting with answering questions displayed, known disease data adjusted the rules made to match the symptoms of eye disease and gave a percentage value and can conclude the type of eye disease suffered by patients to know the value of the approach type of the patient's illness.